2005
DOI: 10.1038/ng1496
|View full text |Cite
|
Sign up to set email alerts
|

An aspartic acid repeat polymorphism in asporin inhibits chondrogenesis and increases susceptibility to osteoarthritis

Abstract: Osteoarthritis is the most common form of human arthritis. We investigated the potential role of asporin, an extracellular matrix component expressed abundantly in the articular cartilage of individuals with osteoarthritis, in the pathogenesis of osteoarthritis. Here we report a significant association between a polymorphism in the aspartic acid (D) repeat of the gene encoding asporin (ASPN) and osteoarthritis. In two independent populations of individuals with knee osteoarthritis, the D14 allele of ASPN is ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
395
3
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 424 publications
(426 citation statements)
references
References 35 publications
20
395
3
8
Order By: Relevance
“…Because the biologic rationale for involvement of ASPN in OA susceptibility is very strong and is based solely on the functional properties of asporin, Kizawa and coworkers (13) decided to test ASPN for association with OA. They not only observed a genetic association with an aspartic acid repeat but also demonstrated that it is abundantly expressed in OA articular cartilage and found that asporin inhibits the expression of the genes encoding aggrecan and type II collagen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the biologic rationale for involvement of ASPN in OA susceptibility is very strong and is based solely on the functional properties of asporin, Kizawa and coworkers (13) decided to test ASPN for association with OA. They not only observed a genetic association with an aspartic acid repeat but also demonstrated that it is abundantly expressed in OA articular cartilage and found that asporin inhibits the expression of the genes encoding aggrecan and type II collagen.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, asporin suppresses TGF␤-mediated expression of the genes encoding 2 cartilage structural component genes, aggrecan and type II collagen, and reduces proteoglycan accumulation in an in vitro model of chondrogenesis. Kizawa and coworkers (13) reported significant association between a polymorphism in the aspartic acid (D) repeat in the asporinencoding gene (ASPN) and knee and hip OA, in 2 independent populations of Japanese individuals. The effect on TGF␤ activity is allele specific, with the D14 allele resulting in greater inhibition than that associated with other alleles.…”
mentioning
confidence: 99%
“…An ASPN allele with a 14-aspartic acid repeat in the N-terminal region, was designated as D14. The frequency of the D14 allele was found to increase with disease severity, and the effect of ASPN on TGF-β activity was allele-specific (15). However, the exact roles of ASPN responsible for tumor cell proliferation and migration and the specific molecular mechanisms have not been fully elucidaded.…”
Section: Introductionmentioning
confidence: 99%
“…Candidate gene studies, meanwhile, have focused mainly on such genes as those encoding collagens, matrix metalloproteinases (MMPs), noncollagenous matrix proteins, cytokines, and the vitamin D receptor, with few showing strong or consistent evidence of association with OA in different samples (15). A recent Japanese candidate gene study, however, has implicated the asporin gene in both hip and knee OA, although it is still unclear whether the findings are generalizable to other groups (16). Therefore, since few validated genes have been found and since the ones that have been found account for only a small proportion of the genetic effect, it is highly likely that as-yet-unknown genes also contribute to OA susceptibility (2).…”
mentioning
confidence: 99%